Penentuan Tingkat Kekerasan Batuan Menggunakan Metode Seismik Refraksi di Jatikuwung Karanganyar - Nakif Nurcandra; Darsono D; Sorja Koesuma (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
It has been done a research about the determination of rock hardness level by using refraction seismic method in Jatikuwung Karanganyar. The research is done by using Seismograph PASI 16S24-P with the path length of 48 meters, distance between geophone 2 meters, 5 shots in each spread and there are four surveys part totally. The processing data is done by using SeisImager software with Plotrefa and Pickwin95 program.We use intercept time method for data processing. The determination of rock hardness use Gardner’s relationship formula. Based on interpretation, there are three layers lithology structure with P wave propagation velocity of 200-1800 m/s and its density of 1.17–1.93 gr/cc. Based on velocity analysis we determine the velocity of first layer is 200-700 m/s, second layer 700-1500 m/s, and third layer 1500-1800 m/s. The subsurface hardness lithology consists of top soil, sands and unsaturated pebble (1.17–1.59 gr/cc) with the depth 2–4 meters in the first layer, saturatedsands, saturated pebble, and alluvium (1.59–1.93 gr/cc) with the depth 9.5–11.5 meters in the second layer, and clay and sands (1.93–2.02 gr/cc) with the depth of 5.5–6 meters in the third layer. The rock hardness is located at the depth betwen 12 – 20 meters.